Optimization of the Unit I Performance to Uncover Criminal Acts of Theft in the Jurisdiction of the Pati City Resort Police - Silitonga, Jonathan (Advances in Police Science Research Journal, 2024)
The aim of this study is to focus on the improvement of the performance of the personnel of the Unit Kamsel Polres Pati in the implementation of Dikmas Lantas activities carried out in order to reduce the number of traffic violations in the territory of the law of Polresta Pati with the hope of increasing performance than the staff of the unit Komsel. In the writing of this final task, the author uses several concepts and theories as analyzing knives such as performance concepts, optimization concept, traffic infringement concept, the concept of Lantas. The theories used are management theory, management elements and SWOT theory The approach used in this study is a qualitative approach. Data collection techniques are carried out using observation techniques, interviews, and document study. Data analysis techniques are performed using data reduction techniques, data measurement. Based on the results of the research that has been done by the author is the performance produced by the unit camel through the Dikmas Lantas activities in order to lower the number of traffic violations is still far from the implementation of its ideal dikmas lantas because of the presence of some changes in the situation in the region such as the example of the execution that is less than maximum due to the concentration of Polri on the vaccination covisd-19 against the community so that the focus on dikmaslantas decreases and some mistakes such as his choosing the target for the performance of dikmeslantas carried out by the Unit Kamsel Polresta Pati as well as not in accordance with the plan of activities that have been made. It can be concluded that the performance of the Kamsel Unit Polresta Pati through Dikmas Lantas in order to prevent traffic violations can still be improved by paying attention to several factors. As well as in terms of the implementation of Dikmas Lantas activities that the Unit of Kamsel Polres Pati has done, it is necessary to pay attention to the stage of its implementation.